Dancing with the patient: a qualitative study of general practitioners’ experiences of managing patients with multimorbidity and common mental health problems - C. Kappelin; C. Sandlund; J. Westman; C. Wachtler (BMC Primary Care, 2023)
Abstract Background Patients with multimorbidity, having two or more chronic diseases, suffer frequently from undiagnosed common mental health problems and are an increasing challenge in primary care. There is a call to improve care delivery to address all these patients’ needs at the same time. The aim of this study was to identify general practitioners’ experiences of managing patients with multimorbidity and common mental health problems in primary care. Methods We conducted five focus group interviews with 28 physicians (3–8 participants in each group) in 5 primary care practices in and outside of Stockholm, Sweden. We used a semi-structured interview guide, and we analysed the data using reflexive thematic analysis. The methodological orientation of the study was inductive, latent constructivism. Results We generated two themes from the data: Unmet patient needs and fragmented care send patients and physicians off balance and Dancing with the patient individually and together with others leads to confident and satisfied patients and physicians. The two themes are related as general practitioners expressed a need to shift from disease-specific fragmentation to relational continuity, teamwork, and flexibility to meet the needs of patients with multimorbidity and common mental health problems. Conclusions These findings can provide guidance in developing future interventions for patients with multimorbidity and common mental health problems in primary care in general, and in Sweden in particular.